Protection of the National Security and Preservation of Basic American Rights: Comments on the Report of the Commission on Government Security - Samuel H. Liberman (Washington University Law Quarterly, 1958)
On June 21, 1957 the Commission on Government Security, established by joint resolution of the Senate and House of Representatives," filed its report with the President and the Congress. Legislation to implement the recommendations contained in the report was introduced both in the House of Representatives and the Senate sometime after the report was filed, but because other important controversial matters were then pending and because adjournment was imminent, no action was taken thereon during the first session of the 85th Congress. However, since legislation based upon the report will probably be introduced at the second session of the 85th Congress, which began in January of 1958, some comment on the conclusions reached by the Commission may prove to be of interest to the Bar at this time.
Keywords: Loyalty oaths